Job quality and precarious employment among lesbian, gay, and bisexual workers: A national study - David J. Kinitz; Faraz Vahid Shahidi; Lori E. Ross (SSM: Population Health, 2023)
Background: Employment outcomes among sexual minority (i.e., lesbian, gay, bisexual) workers are poorly understood, and previous research on this topic has focused almost exclusively on inequities in earnings, neglecting other important dimensions of job quality. We address this gap by describing and comparing the job quality of straight and sexual minority workers in Canada. Methods: Data are from the 2016 General Social Survey: Canadians at Work and Home, the only national survey providing both a measure of sexual orientation and a multidimensional view of job quality in Canada. We identified 25 unique job quality indicators (e.g., temporary employment; job insecurity; health benefits; low income; job satisfaction; job control; discrimination). Latent class cluster analysis was used to establish a typology of job quality describing standard, flexible, and precarious employment types. We used multivariable regression methods to examine the association between sexual orientation and job quality. Results: Sexual minorities reported lower job quality than their straight counterparts along many dimensions, with bisexual people reporting the lowest job quality. While inequities were generally observed among both sexual minority men and women, they sometimes differed in magnitude by gender. The prevalence of precarious employment was nearly three times higher among lesbian, gay, and bisexual workers (PR: 2.94, CI: 1.89–4.58 among all sexual minorities; PR: 3.04, CI: 1.71–5.43 among gay/lesbian workers; and PR: 2.81, CI: 1.45–5.47 among bisexual workers) compared to their straight counterparts. Conclusion: Inequities in job quality among sexual minorities persist despite comprehensive human rights protections in Canada. These inequities are pervasive, extending well beyond conventional indicators such as dollars earned and hours worked. Multi-pronged interventions are needed that move beyond simply ensuring that sexual minority workers are employed. Sexual minority workers deserve access to secure, well-paid work with benefits where they can foster connection and be free from discrimination.